HPV RNA in situ hybridization can inform cervical cytology‐histology correlation. Issue 8 (5th July 2018) - Coppock, Joseph D.; Willis, Brian C.; Stoler, Mark H.; Mills, Anne M.
Abstract : BACKGROUND: In situ hybridization for human papillomavirus (HPV) messenger RNA (HPV RNA ISH) recently was introduced as an ancillary tool in the diagnosis of cervical squamous intraepithelial lesions, and can aid in the distinction between low‐grade squamous intraepithelial lesions (LSILs) versus reactive/negative biopsies. Prior work has shown that up to one‐half of cases originally diagnosed as LSIL are reclassified as negative/reactive by expert consensus review of morphology, and negative HPV RNA ISH results most often correlate with an expert diagnosis of negative/reactive. Given that LSIL overdiagnoses on biopsy may result in the erroneous clinical impression that a cervical lesion has been sampled appropriately, the authors proposed that HPV RNA ISH can inform cytology‐histology correlation for challenging LSIL biopsies. METHODS: A total of 92 cervical biopsies originally diagnosed as LSIL were reviewed by 3 gynecologic pathologists and reclassified based on consensus opinion of morphology. ISH was performed for high‐risk and low‐risk HPV E6/E7 mRNA. Prior/concurrent cytology results were collected. RESULTS: Based on expert consensus morphologic review, 49% of biopsies (45 of 92 biopsies) originally diagnosed as LSIL were reclassified as negative, 6.5% (6 of 92 biopsies) were reclassified as high‐grade squamous intraepithelial lesion, and 44.5% (41 of 92 biopsies) were maintained as LSIL. The majority of LSIL biopsies reclassified as negative (80%; 36 of 45 biopsies) were HPV RNA negative, whereas 93% of LSIL biopsies (39 of 41 biopsies) and 100% of high‐grade squamous intraepithelial lesion biopsies were HPV RNA positive. CONCLUSIONS: LSIL often is overdiagnosed by morphology on biopsy, potentially leading to the false impression that a lesion identified on cytology has been sampled. Performing RNA ISH on biopsies decreases histologic LSIL overdiagnosis, and potentially can prompt further sampling when there is cytology‐histology discordance. Cancer (Cancer Cytopathol) 2018. © 2018 American Cancer Society. Abstract : Low‐grade squamous intraepithelial lesion (LSIL) often is overdiagnosed by morphology on biopsy, potentially leading to the false impression that a lesion identified on cytology has been sampled. Performing RNA in situ hybridization on biopsies decreases the histologic overdiagnosis of LSIL, and can potentially prompt further sampling when there is cytology‐histology discordance.